Anfíbios anuros associados às bromeliáceas nos Estados do Rio de Janeiro e Espírito Santo - Peixoto, Oswaldo Luiz (1977)
The kinds of associations between frogs and bromeliads found in "restingas" (littoral scrub formations) and rain forests in the states of Rio de Janeiro and Espirito Santo have been studied. The anuran species found in association with bromeliads could be arranged in the following categories : fortuitous bromeliadicolous: Bufo granulosus pygmaeus Myers & Carvalho, Hyla rubra altera B. Lutz, Hyla similis Cochran, Phrynohyas mesophea (Hensel) and Trachycephalus nigromaculatus Tschudi; strict bromeliadicolous: Aparasphenodon brunoi Miranda Ribeiro, Hyla albofrenata A. Lutz, Hyla cuspidata A. Lutz and Hyla truncata Izecksohn; bromeliadigenous with direct development and dorsal incubatory pouch: Gastrotheca fissipes (Boulenger ); bromeliadigenous with direct development, which lay eggs: Eleutherodactylus nasutus A. Lutz and Eleutherodactylus venancioi B. Lutz; bromeliadigenous with free tadpole stage, having a dorsal incubatory pouch: Flectonotus fissilis (Miranda Ribeiro) and Flectonotus goeldi (Boulenger); bromeliadigenous with free tadpole stage, laying eggs, with larvae that do not search for food: Dendrophryniscus brevipollicatus Jiménez de la Espada, and bromeliadigenous with free tadpole stage, laying eggs, with larvae that search for food: Crossodactylodes pintoi Cochran, Hyla perpusilla Lutz & Lutz and Phyllodytes luteolus (Wied). Bromeliadicolous are here considered the species that are not associated with bromeliads by any means during their reprodutive cycles, and bromeliadigenous the species which are born in the bromeliads. The descriptions of the tadpole of the following bromeliadigenous species were presented: Dendrophryniscus brevipollicatus Jiménez de la Espada, Flectonotus fissilis (Miranda Ribeiro), Flectonotus goeldi (Boulenger ), Hyla perpusilla Lutz & Lutz, Phyllodytes luteolus (Wied) and Crossodactylodes pintoi Cochran. A key for identification of these larvae is also presented. Some characters such as a depressed body, an interrupted row of upper teeth and the absence of papillae on the anterior part of the upper lip may be considered as an adaptation to the "habitat bromelia" but they are not fully established nor is their meaning very clear. The possibility of competition among tadpoles, especially between species with larvae that must get food in order to complete their larval cycles, is discussed to some extent. Some bromeliads have been indicated as refuge for some species of anurans; this may eventually lead to the determination of a possible association between them. The hatching stages for Gastrotheca fissipes (Boulenger), Flectonotus goeldi (Boulenger) and Flectonotus fissilis (Miranda Ribeiro) were determined as a froglet, for the first species, and as a tadpole in which the beginning of the hind legs are present, for the other two.